IMPLEMENTASI UNDANG-UNDANG NOMOR 2 TAHUN 2011 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 2 TAHUN 2008 TENTANG PARTAI POLITIK TERKAIT DENGAN FUNGSI PENDIDIKAN POLITIK (STUDI KASUS PSI) - Thamiana, Annisa; Maharani, Andina Elok Puri (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
This study analyzes and examines the implementation of political education as a form of implementation of the functions of political parties to create political participation for the community as a form of people sovereignty in Indonesia as a democratic country. This research is a descriptive empirical legal research to find out the implementation of political education by PSI in Kebumen Regency. This study uses primary data in the form of interviews and secondary data consisting of primary and secondary legal materials.This research shows that Indonesia as a rule of law has formed a regulation on political parties, in which political parties are one of the parties participating in the implementation of a democratic state that is manifested in general elections, so as to realize the sovereignty of the people in Indonesia in organizing general elections, there must be political participation from the community which is done by political parties in carrying out the functions of political parties through good political education.